Repetitive pulsed-wave ultrasound stimulation suppresses neural activity by modulating ambient GABA levels via effects on astrocytes - Mishima, Tatsuya; Komano, Kenta; Tabaru, Marie; Kofuji, Takefumi; Saito, Ayako; Ugawa, Yoshikazu; Terao, Yasuo (Frontiers in Cellular Neuroscience, 2024)
Ultrasound is highly biopermeable and can noninvasively penetrate deep into the brain.Stimulation with patterned low-intensity ultrasound can induce sustained inhibition of neural activity in humans and animals, with potential implications for research and therapeutics. Although mechanosensitive channels are involved, the cellular and molecular mechanisms underlying neuromodulation by ultrasound remain unknown. To investigate the mechanism of action of ultrasound stimulation, we studied the effects of two types of patterned ultrasound on synaptic transmission and neural network activity using whole-cell recordings in primary cultured hippocampal cells. Single-shot pulsed-wave (PW) or continuous-wave (CW) ultrasound had no effect on neural activity. By contrast, although repetitive CW stimulation also had no effect, repetitive PW stimulation persistently reduced spontaneous recurrent burst firing. This inhibitory effect was dependent on extrasynaptic-but not synaptic-GABAA receptors, and the effect was abolished under astrocyte-free conditions. Pharmacological activation of astrocytic TRPA1 channels mimicked the effects of ultrasound by increasing the tonic GABAA current induced by ambient GABA. Pharmacological blockade of TRPA1 channels abolished the inhibitory effect of ultrasound. These findings suggest that the repetitive PW low-intensity ultrasound used in our study does not have a direct effect on neural function but instead exerts its sustained neuromodulatory effect through 4 modulation of ambient GABA levels via channels with characteristics of TRPA1, which is expressed in astrocytes.